2009
DOI: 10.1111/j.1399-5448.2009.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

A personalized approach to exercise promotion in adolescents with type 1 diabetes

Abstract: Purpose This exploratory study tested the feasibility of conducting a novel, personalized exercise intervention based upon the current fitness levels of adolescents with type 1 diabetes (T1DM). The relationships of perceptions of benefits and barriers to exercise, exercise self-efficacy and family support to exercise adherence and changes in cardiovascular (CV) fitness, quality of life (QOL), and glycemic control were studied. Methods Adolescents who were sedentary received a graded exercise test to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(93 citation statements)
references
References 45 publications
4
88
1
Order By: Relevance
“…Interestingly, these authors observed that although physical activity improves insulin dosage regimens in youth with T1D, the effect of physical activity on glycemic control is limited. Others have promoted the use of family-based intervention strategies to engage youth in moderate to vigorous physical activity in order to enhance fitness levels and minimize future cardiovascular risk in youth with T1D (Faulkner, 2010; Faulkner et al, 2006; Faulkner, Michaliszyn, & Hepworth, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these authors observed that although physical activity improves insulin dosage regimens in youth with T1D, the effect of physical activity on glycemic control is limited. Others have promoted the use of family-based intervention strategies to engage youth in moderate to vigorous physical activity in order to enhance fitness levels and minimize future cardiovascular risk in youth with T1D (Faulkner, 2010; Faulkner et al, 2006; Faulkner, Michaliszyn, & Hepworth, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…346,[355][356][357] Small studies have reported that aerobic and strength training yields increased fitness and decreased daily insulin dosage compared with normal daily activities 358 and that greater PA improves fitness without changing HbA 1c . 359 In a large study of overweight/obese and sedentary children, 3 months of aerobic training yielded dose-dependent improvements in IR and adiposity compared with usual PA.…”
Section: Exercisementioning
confidence: 99%
“…Faulkner et al recruited 12 T1D sedentary adolescents for a 16 week personalized exercise prescription study with the prescription provided based on current fitness level for each subject. 27 During the study period, subjects were advised to perform 60min of moderate to vigorous physical activity each day wearing an ActiGraph™ Accelerometer (model GT1M, Pensacola, FL, USA). This intervention improved VO 2 max in the cohort.…”
Section: Physical Activity Capture Device Use For Longer Periods In T1dmentioning
confidence: 99%